14-3-3 phosphoprotein interaction networks – does isoform diversity present functional interaction specification? - Paul, Anna-Lisa; Dension, Fiona C.; Schultz, Eric R.; Zupanska, Agata K.; Ferl, Robert J. (Frontiers in Plant Science, 2012)
The 14-3-3 proteins have emerged as major phosphoprotein interaction proteins and thereby constitute a key node in the Arabidopsis Interactome Map, a node through which a large number of important signals pass. Throughout their history of discovery and description, the 14-3-3s have been described as protein families and there has been some evidence that the different 14-3-3 family members within any organisms might carry isoform specific functions. However there has also been evidence for redundancy of 14-3-3 function, suggesting that the perceived 14-3-3 diversity may be the accumulation of neutral mutations over evolutionary time and as some 14-3-3 genes develop tissue or organ specific expression. This situation has led to a currently unresolved question – does 14-3-3 isoform sequence diversity indicate functional diversity at the biochemical or cellular level? We discuss here some of the key observations on both sides of the resulting debate, and present a set of contrastable observations to address the theory that sequence diversity does lead to functional diversity among 14-3-3 isoforms. The resulting model suggests strongly that there are indeed functional specificities in the 14-3-3s of Arabidopsis. The model further suggests that 14-3-3 diversity and specificity should enter into the discussion of 14-3-3 roles in signal transduction and be directly approached in experiments designed to address 14-3-3 functional roles. It is hoped that future studies involving 14-3-3s will continue to address specificity in experimental design and analysis.